Study of Thrombin-Coagulase - Soulier, J. P; Prou-Wartelle, Odette; with the technical assistance of; Hallé, Liliane (Thrombosis and Haemostasis, 1967)
The preparation of thrombin-coagulase is described. The properties of thrombin-coagulase are compared with those of biothrombin: kinetics, thermostability, adsorption, chromatography, esterase activity, clotting activity, action on platelets and on factors V and VIII, susceptibility to inhibitors.Biothrombin and thrombin-coagulase are closely related but distinct. Both apparently derive from prothrombin. Prothrombin and coagulase combine to form a complex: thrombin-coagulase wherein both factors are necessary for its activity. Possible explanations for the difference between thrombin-coagulase and biothrombin are proposed.